Self-assembled nanonization of fatty acid-conjugated vaccine antigen for enhanced thermal stability - Kim, Yeon Ho; Park, Chulhun; Nguyen, Hy D.; V Ngo, Hai; Lee, Beom Jin (International Journal of Pharmaceutics, 2024)
The aim of this study was to evaluate the enhanced thermal stability and physicochemical properties of fattigated vaccine antigens. High molecular weight influenza hemagglutinin (Heg) was used as a model antigen because of low heat stability requiring cold chamber. Heg was conjugated with long-chain oleic acid (C18) and short-chain 3-decenoic acid (C10) to prepare fattigated Heg. Circular dichroism analysis revealed no significant changes in the three-dimensional structure post-conjugation. In the liquid state, the fattigated Heg was self-assembled into nanoparticles (NPs) due to its amphiphilic nature, with sizes of 136.27 ± 12.78 nm for oleic acid-conjugated Heg (HOC) and 88.73 ± 3.27 nm for 3-decenoic acid-conjugated Heg (HDC). Accelerated thermal stability studies at 60 °C for 7 days demonstrated that fattigated Heg exhibited higher thermal stability than Heg in various liquid or solid states. The longer-chained HOC showed better thermal stability than HDC in the liquid state, attributed to increased hydrophobic interactions during self-assembly. In bio-mimicking liquid states at 37 °C, HOC exhibited higher thermal stability than Heg. Furthermore, solid-state HOC with cryoprotectants (trehalose, mannitol, and Tween® 80) had significantly increased thermal stability due to reduced exposure of protein surface area via nanonization behavior. The current fattigation platform could be a promising strategy for developing thermostable nano vaccines of heat-labile vaccine antigens.
Keywords: Antigens; Drug Stability; Fatty Acids; Fatty Acids, Monounsaturated; Hemagglutinin Glycoproteins, Influenza Virus; Hot Temperature; Hydrophobic and Hydrophilic Interactions; Influenza Vaccines; Nanoparticles; Oleic Acid; Particle Size; Polysorbates; Vaccines, Conjugate; Accelerated thermal stability; Fattigation platform; Fatty acid chain length; Hemagglutinin; Self-assembled nanonization; Vaccine antigen